2013
DOI: 10.1016/j.vaccine.2013.04.071
|View full text |Cite
|
Sign up to set email alerts
|

A novel tetrameric gp3501–470 as a potential Epstein–Barr virus vaccine

Abstract: Infectious mononucleosis and B-cell transformation in response to infection with Epstein-Barr virus (EBV) is dependent upon binding of the EBV envelope glycoprotein gp350 to CD21 on B-cells. Gp350-specific antibody comprises most of the EBV neutralizing activity in the serum of infected patients, making this protein a promising target antigen for a prophylactic EBV vaccine. We describe a novel, tetrameric gp350-based vaccine that exhibits markedly enhanced immunogenicity relative to its monomeric counterpart. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…Vaccination using this glycoprotein suppressed IM, but not latent EBV infection . A tetramer of the gp350 is under development as a future vaccine; it has increased specific immunogenicity without inducing production of polyvalent antibodies .…”
Section: Ebv Vaccination Trials Need Long‐term Follow‐upmentioning
confidence: 99%
“…Vaccination using this glycoprotein suppressed IM, but not latent EBV infection . A tetramer of the gp350 is under development as a future vaccine; it has increased specific immunogenicity without inducing production of polyvalent antibodies .…”
Section: Ebv Vaccination Trials Need Long‐term Follow‐upmentioning
confidence: 99%
“…Cellular entry is initiated by EBV gp350 glycoprotein binding to the virus host cell receptors (CR2/CD21 [6] or CR1/CD35 [7]). gp350 is thought to be a major target of neutralizing antibodies (8)(9)(10), and vaccine development efforts are focused on generating gp350-specific neutralizing antibodies (11)(12)(13)(14)(15). Most immunogens are based on sequences from lab-adapted strains, as are assays used to measure neutralizing antibodies.…”
mentioning
confidence: 99%
“…A soluble N-terminal gp350 fragment (aa 1-470) has been shown to prevent EBV attachment to cells by blocking receptor binding (Nemerow et al 1990). A previous study supported the feasibility of using truncated gp350 protein (residues 1-470) as a promising candidate for prophylactic EBV vaccines (Cui et al 2013).…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, the recombinant gp350 1-443 induced stronger lymphoproliferative responses than RVVgp150. Recombinant gp350 expressed in CHO cells (Cui et al 2013) and measles virus (Mok et al 2012) have been shown to induce significantly high-level production of IL-4 and IFN-γ. The splenocytes from gp350 1-443 -immunized mice also displayed increased production of IFN-γ, TNF-α, IL-4, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation